Politics and Religion: Dichotomy and Correlation in the Context of Indonesian Democracy - Edison R.L. Tinambunan (Seri Filsafat Teologi, 2023)
This paper on politics and religion will show the differences in principle and the relationship between the two. Based on their origin, politics and religion are dichotomous, even though they are both located in the country of Indonesia. For this reason, the exploration of politics derived from philosophy is necessary, and the thoughts of ancient Greek philosophers are the users who are the initial place where politics and religion are implemented together. Meanwhile, the correlation will be shown in justice, honesty, and humility between politics and religion. The trend in Indonesia is the intention to unite politics and religion, which is often considered a democratic system, even though the two are different in both origin and purpose, although they can meet in policy. For this kind of research, the use of philosophical texts of ancient Greek philosophy is imperative and the applicable methodology is qualitative with an interpretive approach that is reflexive following the Indonesian democratic context. This research aims not to mix politics and religion, because the origin and purpose are different, and the domain and system are different, although they can meet in the attitude of wisdom in politics